The principle of fraternity in the correlate of thehuman rights and the social State of law: towards theconstruction of the state of the art of the principle offraternity in the law (2014)
In the constitutional narrative is intended to trace the beginning of the fraternity in the solution to the unleashed tensions between the liberal state, the radical democratic model and modern socialism, presented throughout the nineteenth and early twentieth century and which balance formula was found through the social rule of law. In the narrative of human rights in critical perspective, is intended to establish points of contact and divergence between fraternity and the thesis according to which human rights are the result of struggles of the people, i.e., they are plural collective creations, diverse, with specific social and historical contexts. In this context it is appropriate to speak of a critical theory because the complexity of human rights requires to interpret and to observe them from a relational, holistic and heterogeneous vision that incorporates an integration of human vision. It is said on the particular, that the method for study should show human rights in social groups composed of «ideas, institutions, productive forces and social relations of production, of gender and ethnic, but also in their impure nature having to do with their position, layout, temporality, historicity and narration. In their depth must address their core concept in which there are gaps and values, the development of societies and social practices». All this aims to establish an initial map that defines the state of the art of the principle of fraternity in constitutional law.